Selecting for muscling in swine and resulting effects on carcass traits - Wheat, J.D.; Kropf, Donald H.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Litters farrowed total 147 (25 in 1971, 23 in 1972, 33 in 1973, 32 in 1974 and 34 in 1975); pigs total 1196, 1102 alive at birth 94 (8%) dead at birth. Line differences in loin eye area, backfat thickness and age (adjusted to 220 pounds live-weight) have not been significant. Carcass data collected from 165 barrows indicate the two lines do not yet differ in carcass traits.
Swine Industry Day 1975 is known as Swine Day, 1975
Keywords: Swine; Muscling; Carcass traits; Farrowing